The Making and Unmaking of a Saint : Hagiography and Memory in the Cult of Gerald of Aurillac - Kuefler, Mathew (Book collections on Project MUSE., 2014)
The Making and Unmaking of a Saint traces the rise and fall of devotion to Gerald of Aurillac through a millennium, from his death in the tenth century to the attempt to reinvigorate his cult in the nineteenth century.